Germination and anaerobic metabolism of seeds of Tabebuia cassinoides (Lam.) DC subjected to flooding and anoxia - Kolb, Rosana M. [UNESP]; Joly, Carlos A. (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
Tabebuia cassinoides (Lam.) DC (Bignoniaceae) is an arboreal species common in seasonally or permanently waterlogged areas of the "restinga" forest (a type of forest that occurs on the sandbanks of the coastal plains of southeastern Brazil). The objectives of the present study were to establish seed germination responses of this species to flooding and anoxia and investigate the end products of the anaerobic metabolism of seeds subjected to these conditions, with the goal of understanding the adaptive strategies that enable this species to dominate flood prone areas of "restinga", as well as determine reserves stored in their seeds, Seeds of T cassinoides did not germinate under anoxia or complete submergence, but remained viable under these conditions for 15 and 20 days, respectively. Due to their membranaceous wings, the seeds float very well and reached 100% germination in this condition, an important adaptation to overcome the initial stages of development in flooded habitats. In relation to anaerobic metabolism, ethanol is the most important end product, while lactate is produced in lower concentrations. Seeds of T cassinoides have very little endosperm and the reserves, mainly glycoproteins, lipids and free sugars, accumulate in the cotyledons. Free sugars may provide the substrate for the initial metabolism of seed germination, but the level of these reserves was not enough to allow germination under oxygen deprivation. Possibly, carbohydrate reserves were enough only to maintain seed viability for a relative short period under this condition. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Tabebuia cassinoides; Flooding; Anoxia; Germination; Seed reserves